Application of 3D printing technology in the surgical management of advanced ovarian serous carcinoma: a case report - Xi, Hang; Liu, Chunhui; Tian, Nana; Geng, Min; Hu, Jinfang; Li, Haohao; Pan, Wenbo; Sun, Xiaohong; Cai, Zhihui; Bai, Shasha (Frontiers in Oncology, 2025)
Advanced ovarian serous carcinoma presents significant surgical challenges due to tumor size, deep location, and complex anatomical relationships with surrounding structures. This case report highlights the use of 3D printing technology to improve surgical planning and outcomes in such complex scenarios. A 48-year-old female presented with bilateral ovarian tumors, confirmed as serous cystadenocarcinoma. Preoperative 3D modeling was employed to create a detailed anatomical model based on imaging data. This model provided precise visualization of tumor size, vascular supply, and relationships with adjacent organs, facilitating the development of an optimal surgical plan. During surgery, bilateral ovarian tumors were resected along with the uterus, omen tum, and lymph nodes, achieving complete R0 resection. Postoperatively, the patient recovered well, with no complications or recurrence observed during follow-up. This case underscores the value of 3D printing in enhancing surgical precision and safety in complex gynecological oncology cases. By providing individualized anatomical insights, 3D printing supports preoperative planning, improves patient outcomes, and contributes to advancing precision medicine in surgical practice.